Internationalization Issues in Chinese Firms: One Belt, One Road-Based Perspective - Wu, Xia (Frontiers in Psychology, 2022)
The underlying aim of this study was to investigate the impact of human resource management (HRM) practices, organizational identity, and brand leadership on employee brand-based equity through the mediatory role of brand knowledge dissemination. A questionnaire was adopted to obtain data from 421 employees working in the construction sector of China. The SmartPLS software was used to analyze the data with the help of a structural equation modeling (SEM) technique. The results revealed that HRM practices and organizational identity had a positive and significant relationship with employee brand-based equity, while brand leadership had no direct impact on employee brand-based equity. The results also revealed that brand knowledge dissemination mediated the relationship between independent variables (HRM practices, organizational identity, and brand leadership) and dependent variable (employee brand-based equity). Theoretically, this paper made a valuable contribution by examining the impact of HRM practices, organizational identity, and brand leadership on employee brand-based equity. In terms of practical implications, this study would obviously help the organizations to improve their employee brand-based equity through HRM practices and organizational identity.